2015
DOI: 10.3855/jidc.6200
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in dengue infection

Abstract: Introduction: Dengue is endemic in the tropics, and complications involving organ systems are seen with varying incidence. Methodology: We performed a systematic review. MEDLINE, EMBASE, Scopus SciVerse, Google Scholar, and LILACS were searched for papers providing information on cardiac involvement in dengue. Results: Cardiac involvement is not uncommon in dengue infection and is often transient, but may be associated with significant morbidity and even mortality. Direct viral invasion, immune mechanisms, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 43 publications
(63 reference statements)
0
35
0
4
Order By: Relevance
“…Cardiac rhythm disturbances like sinus node dysfunction, atrioventricular conduction blocks, atrial fibrillation, ventricular tachycardia, and ectopic ventricular beats have been reported in dengue infection (2)(3)(4). In dengue fever, most of the cardiac complications are mild, self-limiting and are underdiagnosed (2).…”
Section: Th -8th Daymentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac rhythm disturbances like sinus node dysfunction, atrioventricular conduction blocks, atrial fibrillation, ventricular tachycardia, and ectopic ventricular beats have been reported in dengue infection (2)(3)(4). In dengue fever, most of the cardiac complications are mild, self-limiting and are underdiagnosed (2).…”
Section: Th -8th Daymentioning
confidence: 99%
“…The spectrum of cardiac manifestations includes self-limiting arrhythmias to myocarditis causing hypotension and pulmonary edema (1,2). Various cardiac rhythm disturbances have been reported in dengue infection (2)(3)(4). Eventhough cardiac involvement is not uncommon, it can cause significant morbidity and mortality (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 Insidens infeksi virus dengue dilaporkan se makin me ningkat, laporan mengenai terjadinya manifes tasi klinis yang atipikal, termasuk keterlibatan/ gang guan jantung juga meningkat. Insidens keterlibatan jantung pada pasien infeksi virus dengue belum diketahui secara pasti.…”
unclassified
“…[5][6][7][8] Gangguan jantung terjadi akibat hipoperfusi, invasi langsung otot jantung, atau akibat respon imunologis. 4,7,9 Gejala klinis keterlibatan jantung pada pasien infeksi virus dengue bervariasi luas, mulai dari tidak bergejala/silent disease hingga miokarditis berat yang menyebabkan kematian. 4,10 Sebelumnya, telah dilakukan berbagai penelitian menggunakan biomarker jantung untuk mengetahui keterlibatan jantung pada infeksi virus dengue.…”
unclassified